2018
DOI: 10.1002/ange.201710734
|View full text |Cite
|
Sign up to set email alerts
|

A One‐Step Route to CO2‐Based Block Copolymers by Simultaneous ROCOP of CO2/Epoxides and RAFT Polymerization of Vinyl Monomers

Abstract: The one-step synthesis of well-defined CO 2 -based diblockc opolymers was achieved by simultaneous ring-opening copolymerization (ROCOP) of CO 2 /epoxides and RAFT polymerization of vinyl monomers using at rithiocarbonate compound bearing ac arboxylicg roup (TTC-COOH) as the bifunctional chain transfer agent (CTA). The double chaintransfer effect allows for independent and precise control over the molecular weight of the two blocks and ensures narrow polydispersities of the resultant blockcopolymers (1.09-1.14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…We have previously reported that Cl − of PPNCl coordinates to Al, facilitates the dissociation of Al-O bonds, and therefore, accelerates ROCOP of CO 2 and epoxides. 53,62 As anticipated, the rate of PO/PA ROCOP decreased significantly without PPNCl (Table 1, entries 1 and 2). Yet, PPNCl showed no obvious effect on PET-RAFT polymerization of MMA.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…We have previously reported that Cl − of PPNCl coordinates to Al, facilitates the dissociation of Al-O bonds, and therefore, accelerates ROCOP of CO 2 and epoxides. 53,62 As anticipated, the rate of PO/PA ROCOP decreased significantly without PPNCl (Table 1, entries 1 and 2). Yet, PPNCl showed no obvious effect on PET-RAFT polymerization of MMA.…”
Section: Resultssupporting
confidence: 70%
“…This interesting phenomenon could be explained by the fast and quantitative axial group exchange reaction between the carboxylate group and (TPP 2-Cl )Al III -Cl, which leads to the rapid and quantitative formation of (TPP 2-Cl )Al III -O 2 C-PMMA (Scheme 3c). 53 Therefore, the ring-opening of PO occurs via nucleophilic attack of [PMMA- 3b), both PPE with alternating structure and PMMA formed in the reaction, while no signals corresponding to junction units could be observed. As determined by 1 H NMR spectroscopy, the conversions of both MMA and PA steadily increased with reaction time.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The large-scale application of CO2 copolymers is still limited due to relatively low catalytic activity and poor thermal and mechanical properties. In past decades, there have been a large number of experimental and theoretical studies on the reaction mechanisms, catalytic efficiency, and the applications of polymers [53][54][55][56][57].…”
Section: Plasticsmentioning
confidence: 99%
“…In the one-pot synthesis of BCPs, we try the combination of RAFT polymerizations of methacrylate monomers (MMA, BMA, and PEGMA) or styrene and ROP of ε-CL. 69,70 our one-pot synthesis method uses ACVA bifunctional free radical initiator instead of traditional free radical initiators combined with ROP catalysts. (Figure 4).…”
Section: Synthesis Of Polyester-based Block Copolymermentioning
confidence: 99%